Comprehensive evaluation of a prospective Australian patient cohort with suspected genetic kidney disease undergoing clinical genomic testing: a study protocol. Issue 8 (3rd August 2019) - Jayasinghe, Kushani; Stark, Zornitza; Patel, Chirag; Mallawaarachchi, Amali; McCarthy, Hugh; Faull, Randall; Chakera, Aron; Sundaram, Madhivanan; Jose, Matthew; Kerr, Peter; Wu, You; Wardrop, Louise; et al.
Abstract : Introduction: Recent advances in genomic technology have allowed better delineation of renal conditions, the identification of new kidney disease genes and subsequent targets for therapy. To date, however, the utility of genomic testing in a clinically ascertained, prospectively recruited kidney disease cohort remains unknown. The aim of this study is to explore the clinical utility and cost-effectiveness of genomic testing within a national cohort of patients with suspected genetic kidney disease who attend multidisciplinary renal genetics clinics. Methods and analysis: This is a prospective observational cohort study performed at 16 centres throughout Australia. Patients will be included if they are referred to one of the multidisciplinary renal genetics clinics and are deemed likely to have a genetic basis to their kidney disease by the multidisciplinary renal genetics team. The expected cohort consists of 360 adult and paediatric patients recruited by December 2018 with ongoing validation cohort of 140 patients who will be recruited until June 2020. The primary outcome will be the proportion of patients who receive a molecular diagnosis via genomic testing (diagnostic rate) compared with usual care. Secondary outcomes will include change in clinical diagnosis following genomic testing, change in clinical management following genomic testing and the cost-effectiveness of genomic testing compared with usual care. Ethics and dissemination: The project has received ethics approval from the Melbourne Health Human Research Ethics Committee as part of the Australian Genomics Health Alliance protocol: HREC/16/MH/251. All participants will provide written informed consent for data collection and to undergo clinically relevant genetic/genomic testing. The results of this study will be published in peer-reviewed journals and will also be presented at national and international conferences.